PENDAMPINGAN PRODUKSI KONTEN PEMBELAJARAN DIGITAL BERBASIS PLATFORM GURUVIRTUAL.ID DI SDS SOEKARNO HATTA - Ratnaningsih, Dewi; Hartono, Hartono; Khotimah, Khusnul (Universitas Padjadjaran, 2023)
The rapid increase in technological and scientific advancements has affected many aspects, including the changing characteristics and learning needs of Generation Z students. One example of this change is the increasing use of digital learning content. Not only does it help overcome post-pandemic learning loss, but also digital learning content that is engaging, easily accessible, and inclusive can boost students' interest in learning. Soekarno Hatta Private Elementary School in North Lampung is one of the schools that recognizes the urgency of the need for digital learning. The school intends to implement and enhance digital learning content. However, despite having produced several learning videos, the teachers at this school do not possess the skills to produce high-quality digital learning content. Therefore, the purpose of this community service activity is to assist in increasing the production of digital learning content through the GuruVirtual.ID platform, a learning platform developed by Muhammadiyah University Kotabumi. To achieve optimal results, two methods were utilized: the mentoring method and the output-based partner participatory method. The mentoring method focuses on implementing learning content workshops, assisting in the preparation of learning scenarios, and guiding the practice of recording and editing learning videos based on the GuruVirtual.ID. In the participation method, partners were directed to produce learning content. In addition to enhancing partners' understanding of digital learning content production, this activity resulted in 16 learning videos produced by seven teachers at the school.